2018
DOI: 10.1016/j.kint.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A sodium-glucose cotransporter 2 inhibitor attenuates renal capillary injury and fibrosis by a vascular endothelial growth factor–dependent pathway after renal injury in mice

Abstract: Multiple large clinical trials have shown that sodium-glucose cotransporter (SGLT) 2 inhibitors reduce the risk of renal events. However, the mechanism responsible for this outcome remains unknown. Here we investigated the effects of the SGLT2 inhibitor luseogliflozin on the development of renal fibrosis after renal ischemia/reperfusion injury in non-diabetic mice. Luseogliflozin significantly suppressed development of renal fibrosis, prevented peritubular capillary congestion/hemorrhage, attenuated CD31-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 36 publications
4
112
0
Order By: Relevance
“…In the present study, hiPSC‐derived erythropoietin‐producing cells were treated with vehicle (2‐hydroxylpropyl‐β‐cyclodextrin; n = 5), 100 nmol/L luseogliflozin ( n = 4), 500 nmol/L luseogliflozin ( n = 4) or 50 µmol/L of FG‐4592 ( n = 3; Cayman, Ann Arbor, MI, USA). We previously showed that treatment with 100 nmol/L luseogliflozin sufficiently blocks SGLT2 in vitro . Previous work also showed that treatment with 50 µmol/L FG‐4592, a selective hypoxia‐inducible factor prolyl hydroxylase inhibitor, consistently increased the erythropoietin levels in the medium.…”
Section: Methodsmentioning
confidence: 92%
“…In the present study, hiPSC‐derived erythropoietin‐producing cells were treated with vehicle (2‐hydroxylpropyl‐β‐cyclodextrin; n = 5), 100 nmol/L luseogliflozin ( n = 4), 500 nmol/L luseogliflozin ( n = 4) or 50 µmol/L of FG‐4592 ( n = 3; Cayman, Ann Arbor, MI, USA). We previously showed that treatment with 100 nmol/L luseogliflozin sufficiently blocks SGLT2 in vitro . Previous work also showed that treatment with 50 µmol/L FG‐4592, a selective hypoxia‐inducible factor prolyl hydroxylase inhibitor, consistently increased the erythropoietin levels in the medium.…”
Section: Methodsmentioning
confidence: 92%
“…Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes . Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis . Additionally, the increased delivery of sodium to the macula densa that results from the inhibition of proximal tubular sodium reabsorption leads (through tubuloglomerular feedback) to a reduction in glomerular hyperfiltration, thereby ameliorating the major mechanism of glomerular injury in obesity and type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis. 17,47,48 Additionally, the increased delivery of sodium to the macula densa that results from the inhibition of proximal tubular sodium reabsorption leads (through tubuloglomerular feedback) to a reduction in glomerular hyperfiltration, thereby ameliorating the major mechanism of glomerular injury in obesity and type 2 diabetes. 33,34,49,50 Given the multiplicity of actions on cardiac, vascular and renal pathways that are relevant to the pathogenesis of HFpEF, it seems unlikely that a benefit of empagliflozin in this condition (if found in this trial) can be ascribed solely to its diuretic effects.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…15 Other reported beneficial kidney effects include suppression of kidney fibrosis, decreased peritubular hemorrhage and fibrosis, reduced hypoxia, and increased renal vascular endothelial growth factor A expression in response to ischemia-reperfusion injury, which could preserve intrarenal perfusion and attenuate ischemic injury. 16 As reviewed elsewhere, the reduction in ischemia-reperfusion risk may have a variety of causes, which remain mainly hypothetical and merit further investigation. 17 With the benefit of hindsight, FDAERS reports of AKI may have reflected: (1) expected changes in eGFR on the basis of known hemodynamic effects and (2) higher risk for AKI in people with diabetes taking SGLT2 inhibitors on the basis of confounding AKI risk factors, including advanced age, greater proportion of men, and higher rates of renin-angiotensin-aldosterone system inhibitor and diuretic use.…”
mentioning
confidence: 99%